Indonesian adaptation of the Student-Life Stress Inventory: Psychometric properties and factor structure - Andria Pragholapati; Tirta Adikusuma Suparto; Asih Purwandari Wahyoe Puspita; Afianti Sulastri (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
The Student-Life Stress Inventory is a standard measurement instrument used to measure sources of stress (frustration, conflict, pressure, change, and self-imposition) and reactions to stress (physiological, emotional, behavioral, and cognitive) developed by Bernadette M. Gadzella. (1991). The purpose of this study was to test the construct validity and construct reliability on the academic stress scale and examine the components and indicators that can construct the academic stress variable. The sample in this study was 127 Nursing Students, Universitas Pendidikan Indonesia. The research data were analyzed through the SPSS program. Based on the results of data analysis, the components and indicators that build the academic stress variable are declared valid and reliable. These results indicate that all components and indicators are able to reflect and construct academic stress variables.